Results of Using Multimedia Tablet Unit Based on Brain Based Learning in English Subject Entitled “All about Me” for Primary School Level 1 Students - Luangjamnong, Saranya; Kidkran, Rattakorn (Ratchaphruek Journal, 2014)
This research aimed to : 1) develop a multimedia tablet Unit based on brain based learning in English subject entitled “All about Me” for primary school level 1 students with an efficiency of 80/80, 2) compare the students’ learning achievement of English subject entitled “All about Me” between learning via multimedia tablet lesson based on brain based learning with traditional approach, and 3) study the students’ satisfaction towards learning by multimedia tablet lesson based on brain based learning. The samples were 50 students at Municipality Three (Yommarat Samakki) School, Muang, district Nakhon Ratchasima. The samples were divided into two groups by cluster random sampling, 25 students used for experimental group and 25 students used for control group. The research instruments were 2 lesson plans; multimedia Tablet Unit based on brain based learning, and the learning achievement test. The satisfaction questionnaire, t-test independent were used for data analysis. The research results revealed that the multimedia tablet Unit based on brain based learning in English subject entitled “All about me” for primary school level 1 students had an efficiency of 83.42/82.22 above 80/80 criteria. The students learning achievement learned by multimedia tablet Unit based on brain based learning was significantly higher than those by traditional approach at the 0.01 level. In addition, the students’ satisfaction towards learning by using multimedia tablet Unit based on brain based learning in English subject entitled “All about me” was rated at a highest level.